The Influence Of General Risk On Consumer Trust, Satisfaction, And Intention To Recommend Halal Products - Charellia Dylan Amara; Alldila Nadhira Ayu Setyaning (International Journal of Economics, Business and Innovation Research, 2024)
This study aims to examine the effect of general risk on trust, consume rsatisfaction, and interest in recommending halal products with Waroeng Steak and Shake as the object. Quantitative methods are used with an objective theory testing approach through statistical analysis of 200 Muslim consumer respondents in Indonesia. The results of the study indicate that general risk has a positive and significant effect on consumer trust, consumer satisfaction, and interest in recommending halal products. In addition, consumer trust also has a positive and significant effect on consumer satisfaction and interest in recommending halal products. This approach emphasizes the importance of managerial strategies that focus on risk management and increasing consumer trust and satisfaction to iincrease interest in recommending Waroeng Steak and Shake halal products.